2013
DOI: 10.1128/jcm.00151-13
|View full text |Cite
|
Sign up to set email alerts
|

Integrating the Xpert MTB/RIF Assay into a Diagnostic Workflow for Rapid Detection of Mycobacterium tuberculosis in a Low-Prevalence Area

Abstract: bThe Xpert MTB/RIF assay is a rapid and fully automated real-time PCR assay. The performance of the Xpert MTB/RIF assay as a primary screening test for urgent clinical specimens was evaluated during a 2-year period. The results showed that replacing smear microscopy with the Xpert MTB/RIF assay facilitates laboratory handling and improves the sensitivity and specificity of Mycobacterium tuberculosis detection. Rapid and accurate diagnosis of tuberculosis (TB) is indispensable to adequately manage the disease a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Fourteen study teams provided anonymised individual-level data from 15 studies for the metaanalysis (Table 1). 21,25,27,29,[30][31][32][33][34][35][36][37][38][39] Descriptive systematic review on association between C T values and smear status Ten studies investigated the association between smear status and C T values ( Figure 1). 11,20,21,26,[33][34][35][36][37][38][39][40] Seven of the ten studies were conducted in sub-Saharan Africa, and HIV prevalence among study participants ranged from 3% to 60%.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourteen study teams provided anonymised individual-level data from 15 studies for the metaanalysis (Table 1). 21,25,27,29,[30][31][32][33][34][35][36][37][38][39] Descriptive systematic review on association between C T values and smear status Ten studies investigated the association between smear status and C T values ( Figure 1). 11,20,21,26,[33][34][35][36][37][38][39][40] Seven of the ten studies were conducted in sub-Saharan Africa, and HIV prevalence among study participants ranged from 3% to 60%.…”
Section: Study Selectionmentioning
confidence: 99%
“…Two studies did not provide information on HIV prevalence. 27,36 Overall studies were of moderate to good quality, although they did not always report on their efforts to minimise bias. Most, however, were consecutive or random collections of samples, and nearly all, except three, did report on the flow of patients in the study (Table 1).…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, silent mutations (i.e., mutations that do not change the amino acid sequence such as 514Phe (TTC/TTT)) in the RRDR have been found that generated false-positive results with Xpert MTB/RIF [8486]. Early reports of false-positive rifampicin resistance in strains later found to be wild-type for rpoB led to modifications of the assay to improve performance [8789]. False-positive results for rifampicin resistance could lead to an incorrect diagnosis of MDR TB and subject patients to longer and less-effective treatment with second-line drugs.…”
Section: Expert Commentarymentioning
confidence: 99%
“…ith interest, we read the paper "Integrating the Xpert MTB/ RIF Assay into a Diagnostic Workflow for Rapid Detection of Mycobacterium tuberculosis in a Low-Prevalence Area" by Deggim et al (1). Based on the failed detection of Mycobacterium tuberculosis complex (MTB) by the Xpert assay (GeneXpert; Cepheid, Sunnyvale, CA) in 3 of 4 culture-positive nonrespiratory specimens, the authors concluded that such specimens may not be suitable for Xpert testing, in particular for paucibacillary samples.…”
mentioning
confidence: 99%